CanDirect: Effectiveness of a Telephone-Supported Depression Self-Care Intervention for Cancer Survivors. Issue 10 (1st April 2021) - McCusker, Jane; Jones, Jennifer M.; Li, Madeline; Faria, Rosana; Yaffe, Mark J.; Lambert, Sylvie D.; Ciampi, Antonio; Belzile, Eric; de Raad, Manon
Abstract : PURPOSE: Depression in post-treatment cancer survivors is common and can impair quality of life. CanDirect is a novel, telephone-delivered depression self-care intervention for cancer survivors. We conducted a randomized controlled superiority trial to compare CanDirect with usual care (UC) in this population. METHODS: Participants completing cancer treatment within the past 10 years who had mild-moderate depressive symptoms with or without major depression were recruited from clinical and community settings in Quebec and Ontario. Permuted block random assignment allocated participants to CanDirect plus UC or to UC alone. Assessments of depression severity (Center for Epidemiological Studies-Depression scale [CES-D]; primary outcome) and secondary outcomes health-related quality of life (Short Form Survey-12 mental and physical component summaries), anxiety symptoms (Hospital Anxiety and Depression Scale), activation (Patient Activation Measure), depression diagnosis (Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders-IV), and health services (self-report) were conducted at baseline, as well as 3 and 6 months (primary time point). Analyses of outcomes were adjusted for covariates using linear regression and missing data by inverse probability weighting. RESULTS: Participants recruited between September 2016 and October 2018 were randomly assigned to CanDirect (n = 121) or UC (n = 124). Among 245 participants randomly assigned, 218 (89.0%) completed the primary outcome at 6 months. CanDirect participants reported less severe depressive symptoms on the CES-D than UC participants at 6 months, adjusted effect size (ES) 0.61 (95% CI, 0.33 to 0.88). CanDirect participants also had significantly greater quality of life, lower anxiety, more activation, and lower rates of depression diagnoses, compared with UC. Exploratory analysis suggested that sex was a modifier of the primary outcome (interaction term P value = .03); the intervention was less effective in men (ES, 0.12; 95% CI, −0.45 to 0.69). CONCLUSION: The findings suggest that CanDirect is an effective method of managing mild-moderate depression symptoms in cancer survivors.